The Influence of Entrepreneurial Motivation and Knowledge on Entrepreneurial Interest in Students of the PIPS Department, University of Riau - Novelia, Rani; Sumarno, Sumarno; Haryana, Gani (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the influence of entrepreneurial motivation and knowledge on entrepreneurial interest in PIPS students at the University of Riau. The type of research used is quantitative research. The data collection method uses a questionnaire or questionnaire method. The population in this study is PIPS students class of 2021 consisting of 115 students from the Economic Education study program, 80 students from the History Education study program and 82 students from the Pancasila and Citizenship Education program. With a total number of 280 students. Data analysis techniques use descriptive analysis and Multiple Linear Regression analysis. The results of the research show that there is an influence of Entrepreneurial Motivation (X1) on Entrepreneurial Interest (Y) in students of the PIPS Department, Class of 2021, Riau University. There is an influence of Entrepreneurship Knowledge (X2) on Entrepreneurship Interest (Y) in students majoring in PIPS Class of 2021 at Riau University. There is an influence of Entrepreneurial Motivation (X1) on Entrepreneurial Interest (Y) in PIPS Department students Class of 2021, Riau University.